(3eYQaI GdOGFQI GdeSeGg HGdOGFQI GdgfOjI GdhGbYI aj TQM GdhbGjIs
(3ChdgG (B:s
(3GdMeO ddg ChdkG hBNQkG hGdUdGI Ydi fHjg eJhGJQkG hHYO adeG cGf eYQaI GdOGFQI GdeSeGg HGdOGFQI GdgfOjI GdhGbYI ai TQM GdhbGjI eeG jYO eYVdkG hjMSH eTcdkG EdJbWJ ef GdehGbY MQakG dJhVjMgG s
(3BNQgG (B:s
(3hbSehG cd ObjbI CjVkG HSfjf hSehG cd hGMO efgG KGfjI hgcPG CYJHQhG GdKhGHJ hGdQhGHY hGdNhGeS heG ahbgG Edi GdYhGTQ aQHY GdOhQI JSYjf LRAkG s
(3HgG fXGe GdJYbjHIs
Keywords: (3Gdabg GdMfajs